The Effect Of Digitalization And Technological Innovation On Mediated Competitiveness By Operational Efficiency On PT Hutama Trans Kencana - Rizky Abdi Fauzan; Zainul Kisman (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2026)
The merchant shipping industry is currently facing a massive digital transformation, where operational efficiency and innovation are key to maintaining a competitive market position. PT Hutama Trans Kencana, as a player in the maritime logistics chain, faces the challenge of increasing operational scale and control complexity, which requires strengthening digital strategies. This study aims to examine the effect of digitalization and technological innovation on competitiveness, with operational efficiency as a mediating variable. This research was conducted at PT Hutama Trans Kencana, involving employees as respondents who understand the company's business and operational processes. A quantitative research approach was used with a survey method, where primary data were collected through structured questionnaires distributed to 54 respondents. The collected data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software to test the direct and indirect relationships between variables. The results show that digitalization and technological innovation have a positive and significant influence on operational efficiency and company competitiveness. Furthermore, operational efficiency is proven to have a significant effect in increasing company competitiveness. The mediation test revealed that operational efficiency plays a role as a partial mediator that strengthens the relationship between digitalization, technological innovation, and competitiveness. These findings emphasize the importance of digital system integration and continuous development of technological innovation to optimize work processes and create a strong competitive advantage in the maritime transportation industry .